Canada-Mexico Trade: An Arranged Marriage Comes Of Age - Laura Dawson (The School of Public Policy Publications, 2015)
If Canada’s interest in the North American Free Trade Agreement was in deepening regional trade integration between our economy and the U.S. and Mexico, then we could say it certainly succeeded — at least for about five years. By 1999, however, Canada’s NAFTA trade had peaked, and it has since only declined as a share of its trade with the rest of the world: from 79 to 66 per cent. Truly free trade with the U.S. has proved elusive — the number of professions granted labour-mobility concessions under NAFTA has gone virtually unchanged for 20 years — and trade irritants continue to rankle on both sides of the Canada-U.S. border (think: country-oforigin labelling and “Buy America” rules). That has left Canada looking to strike more free-trade deals in new, farther-flung markets, as a way of diversifying its export markets. In the meantime, the low-cost labour advantages that Mexico 20 years ago offered its NAFTA partners were soon eroded by Asian emerging-market competitors, particularly China. But while Canada was scouring the globe for promising new bilateral trade partnerships, we overlooked the transformation happening on our doorstep in Mexico: it has become an especially promising emerging market itself. It has a growing consumer base, with its middle class alone exceeding the entire population of Canada. The number of Mexican students in higher education has tripled over the last three decades. Its recent economic growth rates have been 1.5 to two times higher than that of either Canada or the U.S. and its GDP is projected to quadruple by 2050, making it one of the world’s five-largest economies. Mexico has also become an enthusiastic trader, eagerly pursuing new global trade opportunities while persistently calling for the expansion of North American trade linkages, including direct bilateral deals with Canada. Meanwhile, global value chains are increasingly regional in nature, suggesting there exists a great deal of potential in a deeper relationship between Canada and Mexico, rather than each country largely relating to one another through their mutual relationship with the United States. There are a number of barriers in the way of course. Canada is displeased with Mexico’s impediments to Canadian beef imports, and Mexicans remain aggravated over Canada’s heightened visa restrictions. The relationship is tepid and its future uncertain. But the two countries do have a head start in pursuing deeper integration, thanks to the common trade rules and dispute-settlement procedures already established through their partnership in NAFTA, and a closer relationship with one another would help both countries form an effective counterbalance against the U.S. on matters of joint interest. A medium-sized economy like Canada cannot be competitive everywhere. Our greatest advantage lies at home, in North America, where we can advance our role in the regional supply chain. Putting our greatest focus on North America means intensifying our trading relationship with Mexico. Fortunately for us, it happens to be one of the most promising emerging markets in the world.